Molecular detection and characterization of Rickettsia felis, R. asembonensis, and Yersinia pestis from peri-domestic fleas in Uganda - Wilfred Eneku; Bernard Erima; Anatoli Byaruhanga Maranda; Nora Cleary Gillian; Gladys Atim; Titus Tugume; Qouilazoni Ukuli Aquino; Hannah Kibuuka; Edison Mworozi; Christina Douglas; Jeffrey Koehler William; Michael von Fricken Emery; et al. (Infection Ecology & Epidemiology)
Background: Fleas transmit a variety of zoonotic agents whose epidemiology and public health risk remains poorly understood in sub-Saharan Africa, including Uganda particularly outside plague-endemic areas. Common flea-borne zoonotic agents include Rickettsia felis and Yersinia pestis..Objectives: The study aimed at detecting and characterising flea-borne pathogens in peridomestic environments in Uganda.Methods: We collected fleas from domestic animals, chickens, rodents, and homestead environments; pooled them by species, collection time, and host species. A total of 172 pools were analyzed for Y. pestis Pla gene. Further, 62 pools were tested for Rickettsia species gltA, ompA, and htrA genes by PCR and Sanger sequencing.Results: Five flea species were identified: C. canis, C. felis, Echidnophaga gallinacea, Pulex irritans, and X. cheopis. Genus, Ctenocephalides, accounted for 84.8% of fleas collected, mostly found on dogs and goats. The flea species were found across all districts, year-round, with higher numbers collected in dry seasons than rainy seasons. Rattus rattus constituted 74% of rodents captured from human dwellings and was the only rodent species with fleas, where X. cheopis was the predominant species. All 172 pools were negative for Y. pestis. Rickettsia spp. was detected in 29/62 (46.8%) pools by the target genes. Of 25 htrA amplicons sequenced, 4% were identified as R. felis from C. canis, 92% were R. asembonensis from multiple flea species, and 4% were identified as Candidatus Rickettsia senegalensis.Conclusion:The survey identified high pool detection rate of Rickettsia spp. in fleas,suggestingrisk of human exposure and infection. This was the first report of Rickettsia spp. in E. gallinacea and detection of Candidatus R. senegalensis in Uganda.